A framework for describing interference in ubiquitous computing environments - Ricardo Morla (2006)
Future ubiquitous computing environments arelikely to consist of numerous interacting components,many of which will have been developed in isolationfrom each other. Unless appropriate measures aretaken, interference (where a component's behavior in adeployed system differs from its behavior when inisolation) is likely to be commonplace. In this paper weexplore the importance of this problem and presentour work-in-progress on a framework that enablesdesigners, developers, and researchers to describe andthus reason about interference in ubicompenvironments.